COGNITIVE SKILLSANDTHE MODEL OFTHEIREXPRESSION: THE CASE OFTHE CHEMISTRY SUBJECT - Voronovič, Roman (Acta Paedagogica Vilnensia, 2013)
The main purposes of the article are to give a well-founded definition to cognitive skills and to suggest a hypothetical model suitable for assessing the efficiency of cognitive skills development in chemistry lessons. In educological publications and legal acts, skills are often succeeded by competences. This is the reason why the definition of cognitive skills does not gain the necessary attention. Cognitive skills are the object of educology and should not be used as a synonym of cognitive abilities which are the object of psychological research. Cognitive skills are defined as skills needed to self-efficiently gain theoretical and practical knowledge. These skills are developed in the cognitive process and act as learning objectives. The definition and features of cognitive skills become important because of the development and spread of education software.Teaching methods based on ICTusage enable pupils to perform chemistry experiments virtually, without using real equipment and materials. Due to the lack of laboratories at schools or insufficient instruments, it offers a solution of many issues. However, it is still not known what will be the consequence of this kind of learning. Moreover, there is no scientific model suitable for evaluating different teaching methods in chemistry education. The solution is suggested in the present article as a hypothetical model of assessming cognitive skills in teaching chemistry. The model is based on L. W. Ander-son’s and D. R. Krathwohl’s taxonomy of educational objectives and A. V. Usova’s definitions of cognitive skills. The model implements cognitive skills’ features in the taxonomy and enables a researcher to track the level of cognitive skills’ development through chemistry teaching.
Keywords: abilities; skills; cognitive skills; chemistry teaching